Does the church deliver? Perceptions amongst South Africans about the role of the church in the HIV/AIDS field - Van Dyk, P. J. (Verbum et ecclesia, 2007)
The aim of this study was to investigate the perceptions of South Africans regarding the church and their attitudes towards HIV-positive people and condom usage. A semi-structured questionnaire was used to investigate participants’ perceptions and attitudes towards the church, HIV-positive people and condom usage. The questionnaire was completed by 1352 participants from diverse religious and other backgrounds. Results showed that 67.2% of participants (mostly active church goers) were prepared to go to their minister for support (if they were HIV-positive). Views that HIV/AIDS is God’ s punishment, that HIV-infection is the result of a ‘sinful lifestyle’ and the condemnation of condom usage were more prevalent among certain categories of people (eg. those who had not been tested for HIV before, men, persons from rural areas, people of lower education level, the unemployed and in some cases the more active members of the church). A third (33.5%) of the participants believed that religious people would be less prone to HIV-infection than non-religious people. 59.1% participants (mostly women and active church goers) believed that the church is doing its best to support HIV-positive people.